Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1534735419866908
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Immunomodulatory Compounds: A Novel Combinatorial Strategy for Integrated Medicine in Oncology? BAIC Exposure in Cancer Cells

Abstract: The Standardized Cultured Extract of Lentinula edodes Mycelia (also known as Active Hexose Correlated Compound, AHCC) and Wasabia japonica (Wasabi) are natural nutritional supplements known for their immunomodulatory and anticancer potential. The aim of this study was to evaluate the combinatorial effect of the bioactive immunomodulatory compound (BAIC), obtained by combining Wasabi and AHCC, on human breast (MCF-7) and pancreatic (Panc02) adenocarcinoma cell lines. Data obtained revealed that BAIC determines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Investigation of the anticancer activity of the mycelial extracts of Shiitake in combination with specific nutrients or other medicinal mushrooms has revealed positive findings. For example, a combination of the standardized cultured extract of Shiitake mycelia (also known as Active Hexose Correlated Compound, AHCC) and Wasabia japonica (Wasabi) (combinedly called Bioactive Immunomodulatory compound, BAIC) was tested for its effects on breast and pancreatic cancer cells [ 68 ]. The results demonstrated that BAIC at very low concentrations reduced the viability of cancer cells more than either AHCC or Wasabi used alone.…”
Section: Anticancer Effects Of Shiitake and Its Main Medicative Compounds/extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of the anticancer activity of the mycelial extracts of Shiitake in combination with specific nutrients or other medicinal mushrooms has revealed positive findings. For example, a combination of the standardized cultured extract of Shiitake mycelia (also known as Active Hexose Correlated Compound, AHCC) and Wasabia japonica (Wasabi) (combinedly called Bioactive Immunomodulatory compound, BAIC) was tested for its effects on breast and pancreatic cancer cells [ 68 ]. The results demonstrated that BAIC at very low concentrations reduced the viability of cancer cells more than either AHCC or Wasabi used alone.…”
Section: Anticancer Effects Of Shiitake and Its Main Medicative Compounds/extractsmentioning
confidence: 99%
“…The results demonstrated that BAIC at very low concentrations reduced the viability of cancer cells more than either AHCC or Wasabi used alone. The anticancer activity of BAIC was mediated through increasing the G0/G1 population and augmenting the percentage of apoptotic cells by upregulating the expressions of pro-apoptotic proteins [ 68 ]. A study exploring the synergistic effects of combining the mushroom Agaricus bisporus and Shiitake ( Lentinus edodes ) on prostate cancer cells demonstrated significant reduction of IL-8, NFkB and nuclear to cytoplasmic ratio, suggesting an enhanced anticancer efficacy of this combined formulation [ 69 ].…”
Section: Anticancer Effects Of Shiitake and Its Main Medicative Compounds/extractsmentioning
confidence: 99%
“…This product was developed by Amino Up Chemical Co. Ltd. (Sapporo, Japan) in Japan in 1992. Several articles describe its therapeutic effects in both in vitro assays and in human and animal studies, including modulation of the immune response, antioxidant and anticancer activity, and prevention of infectious processes [179][180][181][182][183][184][185][186][187]. Leishmaniasis patients could benefit from some of these reported positive effects, such as increased Th1 cell responses [179][180][181], increased production of IL-17 and IFN-γ by CD4+ T cells [180], and modulation of the immune response in intestinal epithelial cells and macrophages [183].…”
Section: Domestic Dog Canis Familiarismentioning
confidence: 99%
“…The cytotoxic effect of the compounds was determined by MTT assays performed on THP-1 and A549 (CCL-185TM) cells after 24 h exposure. [56] Cells were seeded at the density of 1 × 10 4 cells/well into 96-well flat-bottomed plates in 200 μL of RPMI medium and then exposed for 24 h to the compounds at the concentrations resulted synergistic in checkerboard assays. Unexposed cells were used as negative control.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%